Isolation and Identification of Fungal Diseases of Broad bean (Vicia faba L.) in Ain- Zara region, Tripoli, Libya - Afaf Sawei,; Youssef Azzu,; Alya Duzan,; Abdulnabi Abughania, (AlQalam Journal of Medical and Applied Sciences, 2024)
The study was conducted to determine the incidence of fungal plant diseases on faba bean in some fields located in the Ain – Zara region - Tripoli and to identify the causal agents. A total of one- hundred plants of faba bean were collected during 2020-2021 season from some local farms in Ain – Zara region Tripoli (February – April). Fungal pathogens associated with leaves, stems, pods and roots of faba bean have been isolated and identified. The most important and widespread fungal diseases observed: Chocolate leaf spot, Root rot, Anthracnose, Alternaria blight, Ascochyta blight and Sclerotinia stem rot caused by Botrytis fabae, Fusarium solani F. oxysporum, Colletotrichum spp, Alternaria alternata, Ascochyta fabae and Sclerotinia sp respectively. To reduce the risk of diseases of faba bean, cultural practices should be followed including crop rotation and sowing disease-free seeds, burning of plant debris, destruction of any faba bean volunteer seedlings, good weed control and lowering sowing rate to re¬duce the relative humidity and favors aeration are strongly recommended to minimize the disease severity. اجريت هذه الدراسة لتحديد مدي الاصابة بالامراض النباتية الفطرية علي الفول البلدي في بعض الحقول الواقعة في منطقة عين زارة – طرابلس وتحديد العوامل المسببة لها . تم جمع ما مجموعه مائة نبات من الفول البلدي خلال الموسم 2020-2021 من بعض المزارع المحلية في منطقة عين زارة – طرابلس ( فبراير – ابريل ). تم عزل وتحديد مسببات الامراض الفطرية المرتبطة بأوراق وسيقان وقرون وجذور الفول البلدي . وكانت اهم الامراض الفطرية واكثرها انتشارا : تبقع اوراق الشوكولاتة , عفن الجذور , الانثراكنوز لفحة Alternaria , لفحة Ascochyta , عفن الساق Sclerotinia المسبب عن طريق Botrytıs fabae , Fusarium solani , F. oxysporum , Colletotrichum spp , Alternaria alternata , Ascochyta fabae و Sclerotinia sp علي التوالي